Natural History Collections as Inspiration for Technology. (18th February 2019) - Green, David W.; Watson, Jolanta A.; Jung, Han‐Sung; Watson, Gregory S.
Abstract : Living organisms are the ultimate survivalists, having evolved phenotypes with unprecedented adaptability, ingenuity, resourcefulness, and versatility compared to human technology. To harness these properties, functional descriptions and design principles from all sources of biodiversity information must be collated − including the hundreds of thousands of possible survival features manifest in natural history museum collections, which represent 12% of total global biodiversity. This requires a consortium of expert biologists from a range of disciplines to convert the observations, data, and hypotheses into the language of engineering. We hope to unite multidisciplinary biologists and natural history museum scientists to maximize the coverage of observations, descriptions, and hypotheses relating to adaptation and function across biodiversity, to make it technologically useful. This is to be achieved by developments in meta‐ taxonomic classification, phylogenetics, systematics, biological materials research, structure and morphological characterizations, and ecological data gathering from the collections − the aim being to identify and catalogue features essential for good biomimetic design. Abstract : Biodiversity incorporates millions of potential innovations in materials chemistry, physical structures, and architectures. Natural history museum collections are the physical embodiment of global biodiversity – freely accessible for capturing good ideas about how to harness the physics and chemistry of organisms for use in technology.